2016
DOI: 10.3389/fgene.2016.00116
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Gene Networks from SNP Associated with Triacylglycerol and Phospholipid Fatty Acid Fractions from Ribeyes of Angus Cattle

Abstract: The fatty acid profile of beef is a complex trait that can benefit from gene-interaction network analysis to understand relationships among loci that contribute to phenotypic variation. Phenotypic measures of fatty acid profile from triacylglycerol and phospholipid fractions of longissimus muscle, pedigree information, and Illumina 54 k bovine SNP genotypes were utilized to derive an annotated gene network associated with fatty acid composition in 1,833 Angus beef cattle. The Bayes-B statistical model was util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The PCIT method identifies differences in pairs of correlated gene expression levels to measure a gene’s differential connectivity across levels of a phenotype [ 23 ]. Utilization of both PCIT and WGCNA have enabled a better understanding of the co-regulation of mRNAs and miRNAs for different phenotypes [ 21 , 24 27 ] to better comprehend the biological mechanisms and regulatory processes in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The PCIT method identifies differences in pairs of correlated gene expression levels to measure a gene’s differential connectivity across levels of a phenotype [ 23 ]. Utilization of both PCIT and WGCNA have enabled a better understanding of the co-regulation of mRNAs and miRNAs for different phenotypes [ 21 , 24 27 ] to better comprehend the biological mechanisms and regulatory processes in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A genomic region on chromosome 19 (at 51 Mb) was associated with 15 fatty acid traits (LCFA, MCFA, MUFA, MUFA/SFA, SFA, UFA/SFA, C14:0, C14:1, C16:0, C16:1, C18:1c9, C16:0/C14:0, C16:1/C16:0, C16:1-C18:1/C16:0-C18:0, and C18:0/C16:0). This region was also previously reported to be associated with important fatty acid traits [ 18 , 26 ]. This SNP window contains a good candidate gene—fatty acid synthase ( FASN ).…”
Section: Resultsmentioning
confidence: 61%
“…It has also been reported to be associated with adipose composition, milk fatty acid composition, and milk fat content in many different breeds of cattle. These reports indicated that this gene has a pivotal role and is an important candidate gene for fatty acid composition [ 26 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…in the oxidation of fatty acids, mainly described in skeletal muscle where their expression is higher [19,20]. On the other hand, PPARγ is mainly important for adipogenesis, promoting the proliferation and differentiation of adipocytes and also improve insulin sensitivity through increased liver and muscle glucose uptake and reduced circulation in the bloodstream [21].…”
Section: Gene Regulation Of Lipid Metabolismmentioning
confidence: 99%
“…The PCIT method identifies differences in pairs of correlated gene expression levels to measure a gene's differential connectivity across levels of a phenotype[17]. Both the PCIT and WGCNA approaches have enabled a better understanding of the co-regulation of mRNAs and miRNAs for different phenotypes[15,[18][19][20][21] to better comprehend the biological mechanisms and regulatory processes in lipid metabolism.The aim of this study was to identify candidate regulatory genes and pathways that are regulated by miRNAs and understand the importance of integrative co-expression networks of mRNAs-miRNAs for fat deposition in cattle from a systems biology perspective.…”
mentioning
confidence: 99%